O efeito gastroprotetor da galactomanana de delonix regia e goma guar despolimerizada (Cyamopsis tetragonoloba) em modelo de gastrite aguda induzida por etanol - Souza, Maria de Fáthima de (2023)
Gastritis is considered an inflammatory alteration of the gastric tissue, influenced by the ingestion of food content or harmful substances such as alcohol. Currently, the drugs used for the acute condition of gastritis show limitations regarding prolonged use, such as proton pump inhibitors, which cause vitamin deficiency and hematological changes. In view of this, research related to gastric lesions highlights the therapeutic potential of substances with hydrocolloid capabilities in gastroprotection, such as polysaccharides defined as galactomannans. Galactomannans are described for having amounts of mannose and galactose, which favor the formation of viscous solutions, and may promote gastroprotection. Thus, the present study aimed to evaluate the possible gastroprotective effects of Delonix regia Galactomannan (GM-DR) and depolymerized Guar Gum (GGD), in an experimental model of acute gastritis induced by ethanol. Male Swiss mice (25-30 g) were randomly allocated (n=8) into different groups: saline, ethanol (50%), omeprazole 40mg/kg (OME) and pre-treated with GM-DR and GGD at doses 1 , 3, 10 and 30 (mg/kg). After a 12-hour fast, the animals were pre-treated with GM-DR and GGD and one hour later, the gastric lesion was induced by ethanol. Two hours after the beginning of the protocol, the animals were euthanized and the stomachs removed for macroscopic and histological analyses, myeloperoxidase activity (MPO), reduced glutathione (GSH), malondialdehyde (MDA), tissue hemoglobin and TNF-α and cytokine dosages. IL-1β by Elisa. The results obtained indicated that all pre-treatment doses at doses 1, 3, 10 and 30 (mg/kg) reduced (p<0.05) the rates of hemorrhagic lesions in the gastric tissue of the GM-DR groups (7, 14, 8 and 11%) and GGD (13, 8, 9 and 10%) respectively, when compared to the ethanol group (38%), with better efficacy at dose 1, 10 mg/kg for GM-DR compared to OME (23%). For histological data, GM-DR and GGD reduced edema, epithelial cell loss, cell infiltration and hemorrhage when compared to the ethanol group. MPO levels (UMPO / mg tissue) were reduced at all doses (1, 3, 10 and 30 mg/kg) in the GM-DR group (14, 14, 15 and 9%) and GGD only at the 10 mg/kg dose. and 30 mg/kg (17, 15, 13 and 14%) when compared to the ethanol group (21%). GSH indices (μg/g of tissue) increased in the GM-DR (15, 15, 15 and 19%) and GGD (17, 18, 16 and 19%) groups, respectively, when compared to ethanol (9%). MDA (nmol/ g tissue) was reduced in the GM-DR (14, 16, 13 and 11%) and GGD (14, 14, 15 and 12%) groups only at the dose of 30 mg/kg, when compared to ethanol (21%). Given the data obtained, the dose of 10 mg/kg was chosen to continue the study and it was shown that it attenuated the levels of IL-1β (µg/ml) GM-DR (20%) and GGD (24%) and TNF -α (pg/ml) GM-DR (24%) and GGD (25%) when compared to the ethanol group IL-1β (35%) and TNF-α (35%). Given the above, the gastroprotective effect of galactomannan from Delonix regia and depolymerized Guar Gum is evident in gastric damage induced by ethanol, attenuating inflammatory and oxidative parameters.